Impact of Medical Care on Symptomatic Drug Consumption and Quality of Life in Headache: A One-Year Population Study - Cotta Ramusino, Matteo; De Cillis, Ilaria; Costa, Alfredo; Antonaci, Fabio (Frontiers in Neurology, 2019)
Background: Chronic headache is one of the most common pain conditions, often leading to symptomatic drug overuse. The aim of this study was to provide data on symptomatic drug consumption in an Italian outpatient population, and to describe how the clinical picture of headache may change after headache experts take charge of the care of affected individuals. Methods: 199 adults complaining of chronic headache were recruited through 32 pharmacies in the Pavia health district. Participants underwent four evaluations: a baseline assessment (T0) and three follow-up evaluations performed by a neurologist at 3, 6 and 12 months (T3, T6 and T12, respectively). On each occasion, they underwent a complete neurological assessment and received therapeutic adjustments to achieve better management of their headache. Results: On the basis of a preliminary telephone interview, the prevalence rates of chronic headache and medication overuse headache (MOH) were 16% and 12%, respectively. At 12 months of follow-up, we observed a significant decrease in the frequency of attacks (T0: 9±9/month vs T12: 2±2/month; p<0.001), in the number of days/month with headache (T0: 11±9 vs T12: 4±4; p<0.001), and in single attack duration (T0: 34±30 hrs vs T12: 10±19 hrs; p<0.001). Careful headache management resulted in a significant decrease in analgesic consumption (T0: 12±16 vs T12: 4±6 doses/month; p=0.014), and a significant increase in quality of life, measured using the MIDAS and HURT scales (p<0.001). Conclusions: Headache management by a specialist is more effective than self-treatment, resulting in an overall benefit for headache patients.